Development of a Learning Design Based on Health Cupping Services at Fania Salsabila Health Vocational School, Jambi City - Arvandi Arvandi; Ahmad Syarif; Indryani Indryani (IJOEM: Indonesian Journal of E-learning and Multimedia, 2026)
Background: This research aimed to develop and determine the feasibility of learning design based on health cupping services for students of SMK Kesehatan Fania Salsabila, Jambi City.Aims: This research intends to estimate the value of the development of learning design results based on cupping services.Methods: The research adopts a research and development (R&D) strategy utilizing the ADDIE paradigm, which contains five basic stages: analysis, design, development, implementation, and evaluation. The subjects of the study were 32 students of class XI of nursing. The instruments employed include expert validation sheets, student response questionnaires, and learning outcome tests.Results: The results showed that the level of design validity was 92.4% (very valid category), practicality was 89.7% (extremely practical), and effectiveness was shown through an increase in learning outcomes with an N-gain value of 0.67 (medium category).Conclusion: These data demonstrate that cupping service-based learning strategies are beneficial in increasing students' cognitive, affective, and psychomotor competencies.